Projective connection space - Grebenyuk, M. F.; Klokova, L. F. (Proceedings of National Aviation University (archive), 2003)
The article deals with the differential geometry of (n+l)-dimensional affine space An+l. The three- component distributions (H(M(A))-distributions) of affine space are discussed. The geometrical objects If, {№}, which are quasitenzors of the second order of the three-component distribution, have been constructed. These objects determine the normals of the first kind of the basic distribution by an inner invariant method in the second differential neighborhood of forming element of the three-component distribution. It has been proved that projective connection Tfor the three-component distribution is defined by an inner way in the differential neighborhood of the second order and belongs to the type of the projective connections which are defined by the way ofprojection